3D bioprinting of a hyaluronan bioink through enzymatic-and visible light-crosslinking. (25th September 2018) - Petta, D; Armiento, A R; Grijpma, D; Alini, M; Eglin, D; D'Este, M
Abstract: Extrusion-based three-dimensional bioprinting relies on bioinks engineered to combine viscoelastic properties for extrusion and shape retention, and biological properties for cytocompatibility and tissue regeneration. To satisfy these conflicting requirements, bioinks often utilize either complex mixtures or complex modifications of biopolymers. In this paper we introduce and characterize a bioink exploiting a dual crosslinking mechanism, where an enzymatic reaction forms a soft gel suitable for cell encapsulation and extrusion, while a visible light photo-crosslinking allows shape retention of the printed construct. The influence of cell density and cell type on the rheological and printability properties was assessed correlating the printing outcomes with the damping factor, a rheological characteristic independent of the printing system. Stem cells, chondrocytes and fibroblasts were encapsulated, and their viability was assessed up to 14 days with live/dead, alamar blue and trypan blue assays. Additionally, the impact of the printing parameters on cell viability was investigated. Owing to its straightforward preparation, low modification, presence of two independent crosslinking mechanisms for tuning shear-thinning independently of the final shape fixation, the use of visible green instead of UV light, the possibility of encapsulating and sustaining the viability of different cell types, the hyaluronan bioink here presented is a valid biofabrication tool for producing 3D printed tissue-engineered constructs.